At Gleason's gym - Lewin, Ted (Roaring Brook Press, 2007)
Looks at the action at Gleason's Gym in Brooklyn through the eyes of Sugar Boy, a nine-year-old boxing champion who is following in the footsteps of former Gleason's trainees like Muhammad Ali and Jake La Motta.